Clinical significance of blood pressure ratios in hypertensive crisis in children. Issue 3 (11th January 2012) - Wu, Han-Ping; Yang, Wen-Chieh; Wu, Yung-Kang; Zhao, Lu-Lu; Chen, Chun-Yu; Fu, Yun-Ching
Abstract : Objectives: Hypertensive crisis is categorised into hypertensive urgency and hypertensive emergency. The present work aimed to determine the effect of different gradings of blood pressure (BP) ratios in predicting the severity of paediatric hypertensive crisis. Methods: This was a retrospective case series, based in the paediatric emergency departments of the Changhua Christian Hospital and the Tzu-Chi General Hospital, Taiwan. From 1995 to 2010, the correlation between the severity of hypertension (HTN) and the difference in elevated systolic BP and 99th percentile plus 5 mm Hg (dSBP), the difference in elevated diastolic BP and 99th percentile plus 5 mm Hg (dDBP), dSBP ratio (dSBP/99th percentile plus 5 mm Hg) and dDBP ratio were analysed. A total of 110 children with a first attack of hypertensive crisis were recruited. Results: Patients with hypertensive crisis caused by essential HTN had lower dDBP ratios than the other causes (p=0.033), while those with an oncological aetiology had the highest dSBP and dDBP ratios among all the aetiologies. For clinical presentations, patients with nausea/vomiting and visual impairment presented with higher dSBP ratios than those without the symptoms (both p<0.05), but patients with altered consciousness had higher dSBP and dDBP ratios than those who had clear consciousness (p<0.05). Children with hypertensive urgency had lower dSBP and dDBP ratios than those with hypertensive emergency (both p<0.05). Conclusions: dDBP and dSBP ratios may serve as BP parameters in predicting the severity of paediatric hypertensive crisis. A dSBP ratio greater than 20% may indicate a critical point for severe hypertensive crisis in children.